2017
DOI: 10.1371/journal.pone.0181146
|View full text |Cite
|
Sign up to set email alerts
|

How does mandibular advancement with or without maxillary procedures affect pharyngeal airways? An overview of systematic reviews

Abstract: BackgroundMandibular advancement surgery may positively affect pharyngeal airways and therefore potentially beneficial to obstructive sleep apnea (OSA).ObjectiveTo collect evidence from published systematic reviews that have evaluated pharyngeal airway changes related to mandibular advancement with or without maxillary procedures.MethodologyPubMed, EMBASE, Web of Science, and Cochrane Library were searched without limiting language or timeline. Eligible systematic reviews evaluating changes in pharyngeal airwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…It is reported in the literature that a successful MAD treatment outcome following advancement of the mandible could be a positive predictor for a successful MMA surgery outcome . However, a more recent meta‐analysis considered the degree of maxillary advancement to be a predictor of surgical success rather than successful MAD treatment itself . Studies comparing MAD treatment with MMA surgery for OSA are, nevertheless, limited and inconclusive in this matter.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is reported in the literature that a successful MAD treatment outcome following advancement of the mandible could be a positive predictor for a successful MMA surgery outcome . However, a more recent meta‐analysis considered the degree of maxillary advancement to be a predictor of surgical success rather than successful MAD treatment itself . Studies comparing MAD treatment with MMA surgery for OSA are, nevertheless, limited and inconclusive in this matter.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 However, a more recent meta-analysis considered the degree of maxillary advancement to be a predictor of surgical success rather than successful MAD treatment itself. 11,27,28 Studies comparing MAD treatment with MMA surgery for OSA are, nevertheless, limited and inconclusive in this matter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main drawback of that study was the fact that they had used lateral cephalograms, which do not give us enough information regarding the PAS dimensions, namely one of the most important aspects, the area of pharyngeal constriction, can only be analyzed on axial slices of CBCT or CT images. In their overview of systematic reviews on the topic of the effect of mandibular advancement on pharyngeal airways, Tan et al [19] concluded that more evidence was needed in order to draw conclusions related to the effect of mandibular advancement on pharyngeal airways.…”
Section: Discussionmentioning
confidence: 99%
“…MMA has been frequently reported to be an effective method to treat or reduce OSA severity [9,11,35] and has shown a high treatment success rate (> 85%) [36]. Since mandibular setback surgery is in the reverse direction of mandibular advancement, an objective comparison of previous findings for the two different procedures is needed.…”
Section: Improvement Of Airway Patency By Mmamentioning
confidence: 99%